Virtual Concerts in Learning Oboe-Played Chinese Folk Music: Impact on Performance Proficiency, Perceived Aesthetic Qualities, and Students’ Motivation - Zhang, Yang (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
This study compares the effectiveness of video communication technologies and group chats in virtual reality (VR) as platforms for practising musical skills among students. Additionally, it examines the capacity to convey aesthetic characteristics of musical performance through these two forms of remote communication and the influence of these technologies on student motivation. The research involved 106 senior students from two higher educational institutions in China. Zoom and VRChat served as the instructional platforms for the two experimental groups. The findings did not reveal significant differences in performance mastery. Specifically, the perception of task value demonstrated the most substantial increase, scoring 5.65 compared to 4.81 out of a possible 7; all three pairs of values exhibited significant differences between the groups based on the results of the student’s t-test. Furthermore, a significantly higher sense of immersion and quality of aesthetic experience was observed within the VR group, scoring 4.81 compared to 3.70 out of a possible 5 in the videoconferencing group. Additionally, VR’s greater capability to convey characteristic emotional nuances of music was confirmed by the fact that within the VR group, two out of six distinctive features of Chinese folk music (lyrical, highly artistic aspects and intonation subtlety) were more pronounced than in the videoconferencing group. These results indicate the potential of VR technology to enhance the quality of aesthetic experience as well as the motivation for learning among students in music education, including those studying wind instruments.